Seasonal variation in allelopathic potential of the leaves of Copaifera langsdorffii Desf. - Franco, Danilo Miralha [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Lima Neto, Jose de Sousa [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Dokkedal, Anne Ligia [UNESP]; Rolim de Almeida, Luiz Fernando [UNESP] (Soc Botanica Brasil, 2016)
The deciduous plant Copaifera langsdorffii contains important medicinal compounds which may also be allelopathic and inhibitory to plant growth. The species is endemic to the Brazilian Cerrado where there is pronounced climatic seasonality. In this study we demonstrate the allelopathic capacity of extracts from the leaves of C. langsdorffii and pre-purified fractions of the extract. Analysis by HPLC-PAD-ESI-MS confirmed the presence of quercetin-3-O-alpha-rhamnoside and kaempferol-3-O-alpha-rhamnoside as major components, as well as phenolic acid derivatives of gallic acid. The extracts from samples collected during the wet season were rich in flavonoids and reduced the seed germination rate, root emergence time, and root growth of Sorghum bicolor seedlings. Leaves of C. langsdorffii collected in both the wet and the dry season did not differ in the overall phytotoxic potential of their extracts, but differences detected in tested subfractions seem to indicate subtle seasonal changes in chemical composition. These results indicate that changes in the seasonal water status of the Cerrado induces differential synthesis of compounds with higher allelopathic activity.
Keywords: Fabaceae; flavonoids; HPLC-PAD-ESI-MS; kaempferol-3-O-alpha-rhamnoside; quercetin-3-O-alpha-rhamnoside; root growth